Dying inside - Wentz, Pete, 1979-; Klein, Hannah (Writer) (Headshell : Vault Comics, 2024)
"Ash is a sixteen-year-old girl with even more angst than her idol, Elliott Smith. She's apathetic and therefore believes death is the easiest route to relief. ... Unfortunately, her meticulous plans are ruined when the beautiful knife she buys off a webstore happens to be charmed with a protection spell. Now, Ash has to track down the witch who transformed her clocking out attempt into the worst gift imaginable: immortality"--Page 4 of cover.